Detection of Mulatexin in Local Mulberry Plants (Morus spp.) from Bogor, West Java, Indonesia - Yasinta Ratna Esti Wulandari; Yogiara Yogiara; Isabel Livena Young (HAYATI Journal of Biosciences, 2021)
The mlx56 gene family is found exclusively in the mulberry (Morus spp.) plant, and its role is to defend against insect herbivores, yet it had never been discovered from Indonesia, which has been cultivating mulberry silkworm's (Bombyx mori) feed in order to produce silks. This research focused on studying the expression of mlx56 gene family in local mulberry plants from Bogor, West Java, using different plant organs which were leaf, stem, and root. Each sample was collected from four species of mulberry; Morus alba var. kanva-2, M. alba var. multicaulis, M. bombycis var. lembang, and M. cathayana. Genomic RNA samples were collected and synthesized into cDNA, amplification was done using eight primers of the mlx56 gene family and the products were sequenced. Sequences were then analyzed by BLAST. Results showed diverse mlx56 gene family expression among species of mulberry and plant organs. The mlx56-2, mlx56-4, and mlx56-7, were mostly expressed in all species and organs. The gene mlx56-3, which was not discovered in the previous study, was expressed in M. cathayana leaf and root also in the roots of other species. It was identified as chitinase-like protein LA along with mlx56-5, while other genes were identified as mlx56 based on BLAST.